Green hills of Africa - Hemingway, Ernest, 1899-1961. (New York : C. Scribner, 1963)
Hemingway's first venture into nonfiction, Green Hills of Africa chronicles his adventures on safari in the early 1930s and brings to life the beauty of the wilderness that was, even then, threatened by the incursion of man. Woodcuts, scattered throughout the book, add another dimension to this view of the hard-edged, rugged world of wild Africa.
Keywords: Hemingway, Ernest, -- 1899-1961 -- Travel -- Africa, East; Authors, American -- 20th century -- Biography; Hunters -- Africa, East -- Biography; Big game hunting -- Africa, East; Safaris -- Africa, East